GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI KERJA GURU - Rinto Agustian (UNIVERSITAS BENGKULU, 2016)
The purpose of this study is to describe a Leadership Style Of Principle To Motivate Increase Job Teacher elementary school 04 Sindang Kelingi Rejang Lebong district. The methodused qualitative descriptive study. Subjects were 04 public elementary school principal Sindang Kelingi Rejang Lebong district. Data collection techniques in use is the interview, observation anddocumentation. The results show that the Implementation Leadership Style Of Principle To Motivate Increase Job Teacher Elementary School Negeri 04 Sindang Kelingi Rejang Lebongusing, Leadership Style charismatic and democracy.Keywords: leadership style, principle